Inhaler technique mastery and maintenance in healthcare professionals trained on different devices. (2nd January 2018) - Bosnic-Anticevich, Sinthia; Callan, Christina; Chrystyn, Henry; Lavorini, Federico; Nikolaou, Vasilis; Kritikos, Vicky; Dekhuijzen, P. N. Richard; Roche, Nicolas; Bjermer, Leif; Rand, Cynthia; Zwar, Nicholas; Price, David B.
ABSTRACT: Objective : Healthcare professionals (HCPs) are required to assess and train patients in the correct use of inhalers but are often unable to demonstrate correct technique themselves. We sought to assess the level of training required for HCPs to master and maintain device mastery when using two different dry powder inhalers (DPIs). Methods : We conducted a randomized, un-blinded, crossover study in undergraduate HCPs who undertook a six-step training procedure (intuitive use, patient information leaflet, instructional video, individual tuition from expert, then two repeats of individual tuition) for the use of Turbuhaler® (an established device) and Spiromax® (a newer device, reportedly easier to use). Device mastery (absence of errors) was evaluated by expert assessors at each training step. Maintenance of mastery was assessed 4 ± 1 week (visit 2) and 8 ± 2 weeks (visit 3) after initial training (visit 1). Results : Of 516 eligible participants, 113 (22%) demonstrated device mastery prior to training on Spiromax® compared with 20 (4%) on Turbuhaler® ( p < 0.001). The median number of training steps required to achieve mastery was 2 (interquartile range [IQR] 2–4) for Spiromax® and 3 (IQR 2–4) for Turbuhaler® ( p < 0.001). A higher number of participants maintained mastery with Spiromax® compared with Turbuhaler®, at visits 2 and 3 (64% vs 41% and 79% vs 65%, respectively; p < 0.001). Conclusions : There are significant differences in the nature and extent of training required to achieve and maintain mastery for Spiromax® and Turbuhaler® devices. The implications on clinical practice, device education delivery, and patient outcomes require further evaluation.